2016
DOI: 10.1002/uog.15734
|View full text |Cite
|
Sign up to set email alerts
|

Operator competence in fetoscopic laser surgery for twin–twin transfusion syndrome: validation of a procedure‐specific evaluation tool

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This may be explained by his starting with the first procedures in technically easier cases with posterior placentae, the possibility of immediate intervention by the supervising experienced operator if technical difficulties occurred and a final check as to whether all anastomoses had been coagulated. It is possible that in the future a recently developed procedure‐specific evaluation tool to assess the performance of trainees may be helpful in ensuring that they have reached a sufficient level of competence to perform the procedure unsupervised.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by his starting with the first procedures in technically easier cases with posterior placentae, the possibility of immediate intervention by the supervising experienced operator if technical difficulties occurred and a final check as to whether all anastomoses had been coagulated. It is possible that in the future a recently developed procedure‐specific evaluation tool to assess the performance of trainees may be helpful in ensuring that they have reached a sufficient level of competence to perform the procedure unsupervised.…”
Section: Discussionmentioning
confidence: 99%
“…The findings by Papanna et al are important because they could be useful in establishing guidelines for training future fetoscopic interventionists and developing methods for regular audits of the performance of individual operators or centres. A performance assessment tool for FLP, developed by Peeters et al, (41) included a validated checklist of the essential steps in FLP and also evaluated its use to ensure the competency of future fetal surgeons before they performed the procedure unsupervised, illustrating that operators may reach a level of competence after at least 25 FLP procedures. Previous studies have reported learning curves for FLP by grouping initial series and comparing it to later series.…”
Section: Ttts the Eurofetus Study Demonstrated That Pregnancies Compmentioning
confidence: 99%
“…While there are many commercially available simulators for some areas of medicine, such as laparoscopy (Larsen et al, 2012) and endoscopy (King et al, 2016), the SILICONE project (SImulator for Laser therapy and Identification of Critical steps of Operation: New Education program) aimed to develop a standardized training program for laser therapy for TTTS (Peeters et al, 2015c). This project used Delphi methodology to define 55 substeps essential to the procedure, and then developed an evaluation instrument that was validated using a silicone simulator (Peeters et al, 2015b; Peeters et al, 2015a). The authors concluded that proficiency-based simulator training improves performance for fetoscopic laser therapy, and recommended practice on a simulator prior to carrying out FLP for TTTS in pregnant women.…”
Section: Finding Solutions: Ensuring Procedural Competence and Patienmentioning
confidence: 99%
“…Many types of WBA have been developed, but there continues to be concern about validity and reliability, and the demand on resources when running WBAs (Shalhoub et al, 2014). In regard to fetal therapy, the SILICONE project group has reported good inter-observer reliability and the ability to discriminate experts from novices using the assessment tool they have developed for FLP (Peeters et al, 2015a).…”
Section: Finding Solutions: Ensuring Procedural Competence and Patienmentioning
confidence: 99%